Citrus junos as a host of citrus bacterial canker. (20th June 2017) - ; Jeger, Michael; Caffier, David; Candresse, Thierry; Chatzivassiliou, Elisavet; Dehnen‐Schmutz, Katharina; Gilioli, Gianni; Grégoire, Jean‐Claude; Jaques Miret, Josep Anton; MacLeod, Alan; Navajas Navarro, Maria; Niere, Björn; et al.
Abstract: Following a request from the European Commission, the European Food Safety Authority (EFSA) Plant Health (PLH) Panel analysed a dossier submitted by the Japanese authorities in order to clarify the host status of Citrus junos with regard to Xanthomonas citri pv. citri and Xanthomonas citri pv. aurantifolii, causal agents of citrus bacterial canker, and to indicate whether C. junos fruit could represent a pathway for the introduction of citrus bacterial canker into the European Union. In a previous opinion in the year 2014, the EFSA PLH Panel concluded that commercial fresh citrus fruit is generally pathway and that no commercially important Citrus species or variety can be considered as immune to citrus bacterial canker. In the current assessment, the EFSA PLH Panel analysed the two scientific papers provided by the Japanese authorities, as well as 16 additional papers identified through a systematic literature review. The PLH Panel considered that the conclusions of its previous opinion remain valid and that convergent lines of evidence provide sufficient demonstration that C. junos is a host of X. citri pv. citri and X. citri pv. aurantifolii . Therefore, there is no reason to consider the C. junos fruit differently from other citrus species. Consequently, the assessment of the general citrus fruit pathway from the 2014 opinion still applies. Uncertainties on these conclusions are a result of the scarce scientific evidence published on this subject in addition to the methodological and reporting limitations of the published papers.